Echoes of the Unspoken: A Study of Bowlby’s Attachment Theory and Intergenerational Trauma in Elif Shafak’s The Bastard of Istanbul - Saleem, Iqra; Abbas, Warda (Annals of Human and Social Sciences, 2025)
This research paper aims to investigate fictional representation of intergenerational trauma in Elif Shafak’s The Bastard of Istanbul (2006) using John Bowlby’s “Theory of Attachment”. Shafak’s novel presents an intricately woven plot based on a multigenerational account of complex characters exposed to a heterogeneous blend of traumatic experiences which leave detrimental impact on their following generations. Utilizing Bowlby’s insights, this paper enunciates how remnants of an individual’s trauma are carried forward into his next generation through insecure attachment pattern within a parent-child relationship. After analyzing four consecutive generations of Kazanci family in Shafak’s novel, the study concludes that parent-child attachment relationships between Shafak’s characters are highly insecure and therefore remain instrumental in passing Shushan Kazanci’s complex childhood trauma across her following generations - ultimately leading to her great-granddaughter’s incestuous birth. This vicious chain of intergenerational trauma can only be broken with the victims’ resistance and resilience which Shafak’s characters lack